Chemical Energy‐Driven Lithiation Preparation of Defect‐Rich Transition Metal Nanostructures for Electrocatalytic Hydrogen Evolution. Issue 35 (7th August 2022) - Han, Di; Du, Gaohui; Wang, Yunting; Jia, Lina; Zhao, Wenqi; Su, Qingmei; Ding, Shukai; Zhang, Miao; Xu, Bingshe
Abstract: Transition metal nanostructures are widely regarded as important catalysts to replace the precious metal Pt for hydrogen evolution reaction (HER) in water splitting. However, it is difficult to obtain uniform‐sized and ultrafine metal nanograins through general high‐temperature reduction and sintering processes. Herein, a novel method of chemical energy‐driven lithiation is introduced to synthesize transition metal nanostructures. By taking advantage of the slow crystallization kinetics at room temperature, more surface and boundary defects can be generated and remained, which reduce the atomic coordination number and tune the electronic structure and adsorption free energy of the metals. The obtained Ni nanostructures therein exhibit excellent HER performance. In addition, the bimetal of Co and Ni shows better electrocatalytic kinetics than individual Ni and Co nanostructures, reaching 100 mA cm −2 at a low overpotential of 127 mV. The high HER performance originates from well‐formed synergistic effect between Ni and Co by tuning the electronic structures. Density functional theory simulations confirm that the bimetallic NiCo possesses a low Gibbs free energy of hydrogen adsorption, which are conducive to enhance its intrinsic activity. This work provides a general strategy that enables simultaneous defect engineering and electronic modulation of transition metal catalysts to achieve an enhancement in HER performance. Abstract : Novel chemical energy‐driven lithiation is proposed to synthesize transition metal nanostructures with ultrafine grains of 3–5 nm. By taking advantage of the slow crystallization kinetics, more surface and boundary defects are generated and remained, which reduce the atomic coordination number and modulate the electronic structure and adsorption free energy of the metals for enhanced hydrogen evolution reaction performance.